Correlation of Particle Traversals with Clonogenic Survival Using Cell-Fluorescent Ion Track Hybrid Detector - Dokic, Ivana; Niklas, Martin; Zimmermann, Ferdinand; Mairani, Andrea; Seidel, Philipp; Krunic, Damir; Jäkel, Oliver; Debus, Jürgen; Greilich, Steffen; Abdollahi, Amir (Frontiers in Oncology, 2015)
Development of novel approaches linking the physical characteristics of particles with biological responses are of high relevance for the field of particle therapy. In radiobiology, the clonogenic survival of cells is considered the gold standard assay for assessment of cellular sensitivity to ionizing radiation. Towards further development of next generation biodosimeters in particle therapy, cell-fluorescent ion track hybrid detector (Cell-FIT-HD) was recently engineered by our group and successfully employed to study physical particle track information in correlation with irradiation- induced DNA damage in cell nuclei. In this work, we investigated the feasibility of Cell-FIT-HD as a tool to study the effects of clinical beams on cellular clonogenic survival. Tumor cells were grown on the FNTD as cell culture, mimicking the standard procedures for clonogenic assay. Cell-FIT-HD was used to detect the spatial distribution of particle tracks within colony-initiating cells. The physical data were associated to radiation induced foci as surrogates for DNA double strand breakages (DSB), the hallmark of radiation ‐induced cell lethality. Long‐term cell fate was monitored to determine the ability of cells to form colonies. We report the first successful detection of particle traversal within colony-initiating cells at subcellular resolution using Cell-FIT-HD.